The Effect of Benson and Murottal Al-Qur’an Relaxation Therapy Surah Ar-Rahman on the Quality of Life of Diabetes Mellitus Patients in the Kaliwungu Kudus Health Center Area - Lailatul Karimah; Sukarmin Sukarmin; Umi Faridah (International Journal Of Health Science, 2026)
Diabetes Mellitus is a chronic disease that can reduce the quality of life of patients from physical, psychological, social, and environmental aspects. This study aims to analyze the effect of the combination of Benson relaxation therapy and the murottal Al-Qur’an Surat Ar-Rahman on the quality of life of Diabetes Mellitus patients in the working area of the Kaliwungu Kudus Health Center with a quasi-experimental pretest–posttest control group design. A total of 36 respondents were divided into intervention and control groups of 18 people each, with measurements using WHOQOL-BREF. The results showed that the median quality of life of the intervention group increased from 43.00 to 78.13 after seven days of intervention with a significant Wilcoxon test (p=0.000), while the control group showed no significant change with a median of 39.00 to 40.13 (p=0.068). The Mann–Whitney test showed significant differences between the two groups (p=0.000), so it can be concluded that the combination of Benson relaxation therapy and Qur’anic murottal is effective in improving the quality of life of Diabetes Mellitus patients and has the potential to be applied as a complementary intervention in nursing practice.